Growth and Survival of Mytilopsis adamsi During Larval to Early Juvenile Transition Under Different Salinity Conditions: Pertumbuhan dan Kelangsungan Hidup Mytilopsis adamsi Selama Transisi Larva ke Juvenil Awal pada Kondisi Salinitas yang Berbeda - Ahyani, Dina; Muhklis, Alis; Priyambodo, Bayu (Yayasan Siti Widhatul Faeha, 2025)
Mytilopsis adamsi, a small filter-feeding bivalve mollusk, has become an invasive species cultivated in Indonesia as natural feed for economically valuable crustaceans. This study determined optimal salinity levels for growth and survival of M. adamsi during larval to early juvenile transition. Using a completely randomized design, four salinity treatments (10, 20, 30, and 40 ppt) were tested with three replicates each. Larvae were reared for 28 days with Nannochloropsis sp. and Pavlova lutheri as feed, developing from 50.4 µm to 140.17 ± 6.12 µm. Treatments at 20 and 30 ppt demonstrated optimal performance with identical specific growth rates (SGR) of 3.90% per day. Survival rates showed no significant difference (p > 0.05) between treatments, ranging from 24.6% to 27.8%, with highest values at 40 ppt (27.8 ± 0.4%). Statistical analysis revealed a quadratic relationship for SGR (y = -0.0014x² + 0.0615x + 3.2576, R² = 0.8753) with theoretical optimum at 22.0 ppt. The optimal salinity range for M. adamsi cultivation is 20–30 ppt based on growth performance. These results provide baseline data for commercial cultivation protocols and environmental management strategies.